Islam Wasatiyah as a Form of Religious Moderation: Values, Challenges, and Implementation in Indonesia - Ainun Nafisa; Alpin Iskandar; Bayu Nugraha (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
Religious moderation is a concept that is rooted in the word